Pengaruh Kecerdasan Intelektual, Kecerdasan Emosional, Dan Kecerdasan Spiritual Terhadap Pemahaman PKP Mahasiswa PGPAUD UPBJJ UT Semarang - Badjuri Badjuri; Aini Indriasih; Sri Sumiyati (Universitas Muria Kudus, 2019)
The purpose of this study was to determine the effect of intellectual intelligence, emotional intelligence and spiritual intelligence on PKP understanding and supporting theories. This study uses a Likert model questionnaire instrument, observation, and documentation as a method of data collection. The sample is taken from the population, that is, all PAUD students who take PKP courses at UT Semarang UPBJJ in 2018.1 with a quota sampling technique. Test the validity of the instrument using the Product Moment correlation coefficient, and the reliability test using Cronbach Alpha. The results of the study provide the conclusion that there is an influence between intellectual intelligence on the understanding of PFM by 33%, while Emotional intelligence has an influence of 3.3% on the understanding of PFM and Spiritual intelligence gives an influence of 5.6%. When viewed together, the lack of intelligence gives an effect of 12.2% on the understanding of PKP of PGPAUD students in UPBJJ Semarang.